Quality Analysis and Comprehensive Evaluation of 26 Varieties of Actinidia arguta Fruits - Yuning AN; Yuncai ZHAO; Junwei HUO; Dejiang LIU; Yihong BAO (Shipin gongye ke-ji)
Actinidia arguta was a specialty berry of the Northeast region. We aimed to establish a scientific evaluation method to compare the advantages and disadvantages of the different quality characteristics and to facilitate the comprehensive use of A. arguta resources. In this study, 26 different varieties of A. arguta were used for a comprehensive evaluation of the appearance, nutritional, and functional indices (active substance content, antioxidant capacity, and lipid-lowering ability) of the fruits. The 26 varieties of A. arguta were classified using the clustering heat map analysis method combined with sensory evaluation, and each category of characteristic was analyzed to explore its potential application value. The results showed significant differences in 20 quality indicators among the 26 varieties of A. arguta. Based on the correlation and principal component analysis results, the evaluation indicators were simplified and total phenols, sugar-acid ratio, soluble solid content, iron content, and vitamin C (VC) content were identified as critical indicators for evaluating the quality of A. arguta. Using principal component analysis to establish a comprehensive quality evaluation model for A. arguta, among the 26 samples tested, the five samples with the best comprehensive quality were 'A15', 'Huanyou No.1', 'JL01', 'J061403', and 'J141901', which had great value for targeted cultivation and development processing. After clustering heat map analysis of the 26 varieties of A. arguta into Class Ⅰ, Ⅱ, Ⅲ, Ⅳ, each category contained 6, 13, 2, and 5 varieties, respectively. Class Ⅰ had a high content of active substances and was suitable for the development of high-value-added functional health food products. Class II had superior sensory quality and was suitable for fresh consumption. Class Ⅲ had high VC content and was suitable for the preparation of VC dietary supplements. Class Ⅳ had good processing quality and was suitable for the processing of fruit wine, fruit juice, fruit preserves, jams, canned food, and other general food. A evaluation system established in this study may provide a theoretical reference for selecting and breeding A. arguta varieties and promoting their planting and processing in China.